2017
DOI: 10.3389/fneur.2017.00493
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Optical Coherence Tomography in Neuromyelitis Optica Spectrum Disorders

Abstract: Neuromyelitis optica spectrum disorders (NMOSD) comprises a group of central nervous system disorders of inflammatory autoimmune origin that mainly affect the optic nerves and the spinal cord and can cause severe visual and general disability. The clinical signs are similar to those of multiple sclerosis (MS), with the result that it is often difficult to differentiate between the two, thus leading to misdiagnosis. As the treatment and prognosis of NMOSD and MS are different, it is important to make an accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…[ 228 ] Affected structures include optic nerve and optic chiasm, with the retina being one of the most affected regions due to thinning of peripapillary retinal nerve fiber layer (pRNFL) and retinal ganglion cell-inner plexiform layer (GCIPL). [ 165 ] For several years, a great effort has been dedicated to understanding the role of optic coherence tomography (OCT) as a minimally invasive imaging technique to diagnose NMOSD. In addition, OCT is employed to assess neurodegenerative damage to pRNFL and GCIPL via retinal examination in NMOSD patients.…”
Section: Diagnosis Of Neuromyelitis Opticamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 228 ] Affected structures include optic nerve and optic chiasm, with the retina being one of the most affected regions due to thinning of peripapillary retinal nerve fiber layer (pRNFL) and retinal ganglion cell-inner plexiform layer (GCIPL). [ 165 ] For several years, a great effort has been dedicated to understanding the role of optic coherence tomography (OCT) as a minimally invasive imaging technique to diagnose NMOSD. In addition, OCT is employed to assess neurodegenerative damage to pRNFL and GCIPL via retinal examination in NMOSD patients.…”
Section: Diagnosis Of Neuromyelitis Opticamentioning
confidence: 99%
“…[ 198 ] OCT employs low-coherent light to produce backscattered and reflected cross-sectional high-resolution 3D images of retinal structures that reveal NMOSD-specific intraretinal pathologies, but most importantly, OCT can provide differential diagnosis between MS and NMOSD. [ 165 198 ] In NMOSD patients, acute single ON attack causes more damage to pRNFL and GCIPL layers that can be detected via OCT.[ 146 ] Currently, OCT is widely used to measure NMOSD disease progression course, as well as outcome response to NMOSD neuroprotective therapies. [ 269 ]…”
Section: Diagnosis Of Neuromyelitis Opticamentioning
confidence: 99%
“…RNFLT was significantly thinner in NMOSD-ON and IDON patients six months after an ON attack compared to normal controls. It was reported that NMOSD-ON had no preponderant RNFLT thinning pattern [ 28 ]. In this study, no significant N/T ratio difference was found in NMOSD-ON versus IDON eyes, which means all quadrants were evenly affected in both types of ON.…”
Section: Discussionmentioning
confidence: 99%
“…In how far new technical methods such as the video-oculography, the scanning laser Doppler flowmetry, laser scanning tomography or optical coherence tomography may find their way into routine clinical neuro-ophthalmological praxis even in countries with lower income remains unsettled. [ 39 97 98 99 ]…”
Section: Discussionmentioning
confidence: 99%